Microstructure formation in Waspaloy multilayer builds following direct metal deposition with laser and wire - Nur Izan Syahriah , Hussein; Segal, Joel; McCartney, Graham; Pashby, Ian (2008)
In the manufacture of parts by direct metal deposition it is common to inject powder into a molten pool formed by laser heating. However, a wire feedstock offers potential advantages and was employed in the present study of multilayer deposition of Waspaloy in the form of walls approximately 6 mm thick using a high power diode laser. The macro- and microstructural evolution was investigated and the deposits were characterized by optical microscopy, scanning electron microscopy (SEM), differential scanning calorimetry (DSC) and microhardness testing. A columnar-dendritic solidification structure forms with the dendrites growing approximately in the plane of the wall and at an angle of around 30◦ to the build direction. Layer bands were observed, corresponding to the depth of remelting in each successive pass and are due to localized dendrite arm coarsening. The microhardness of multilayer walls decreases from bottom to top, i.e. along the build direction and also depends on the number of layers in the wall. Although the Ni3(Al,Ti) precipitate phase (y')could not be detected by SEM, DSC thermograms of samples from different positions in the multilayer deposits exhibit different characteristics which are ascribed to variations y' in precipitation. The DSC data are used to interpret the microhardness variations in terms of the complex thermal histories affecting y'formation in the alloy.